A bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material and its preparation method and application

By introducing linear dielectric CLT into BF-BT-based energy storage ferroelectric ceramic materials, it regulates its microstructure and relaxability, solving the problems of low energy storage density and efficiency and poor mechanical properties in existing materials, and achieving the improvement of high energy storage performance and mechanical properties.

CN119241225BActive Publication Date: 2025-04-01CHENGDU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411764149.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-01
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The existing BF-BT-based energy storage ferroelectric ceramic materials have large residual polarization strength, low breakdown field strength and poor mechanical properties, resulting in low energy storage density and efficiency, and poor service stability and reliability.

Method used

By introducing linear dielectric Ca0.7La0.2TiO3 (CLT) into BF-BT lead-free relaxation ferroelectric ceramics, the third component solid solution method is used to regulate the microstructure, phase structure, domain structure and relaxability of the material.

Benefits of technology

The purpose of improving energy storage performance and mechanical properties is achieved, which is specifically manifested in obtaining excellent recoverable energy storage density and energy storage efficiency under a small electric field, enhanced thermal stability and frequency stability, and ultra-high mechanical hardness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241225B_ABST
    Figure CN119241225B_ABST
Patent Text Reader

Abstract

The invention discloses a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material and a preparation method and application thereof, and relates to the technical field of functional materials. The chemical formula of the bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material is (1- x )(0.67BiFeO3‑0.33BaTiO3)‑ x Ca 0.7 La 0.2 TiO3, among which x =0.25~0.40, x Indicates the molar fraction. By means of solid solution of the third component, the linear dielectric Ca 0.7 La 0.2 TiO3 was introduced into BF-BT lead-free relaxor ferroelectric ceramics, and a new multi-component solid solution lead-free energy storage relaxor ferroelectric ceramic material was synthesized by traditional solid phase reaction method: (1- x )(0.67BiFeO3‑0.33BaTiO3)‑ x Ca 0.7 La 0.2 TiO3, to achieve the purpose of improving energy storage and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional materials, and in particular to a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material and a preparation method and application thereof. Background Art

[0002] At present, ceramic dielectric capacitors are widely used in energy storage devices and energy conversion systems due to their ultra-high power density, fast charge and discharge speed, long cycle life and good temperature stability, such as pulse / high-power power supply systems used in various types of IoT electronic devices, hybrid vehicles, weapons and equipment. However, compared with other energy storage devices (such as batteries, electrochemical capacitors, etc.), dielectric capacitors have relatively small energy storage density and low energy storage efficiency, which has become the main factor restricting their rapid development and large-scale application. In view of this, many different types of dielectric capacitor materials have been rapidly developed in recent years. At present, according to the law of the change of the polarization state of dielectric energy storage materials with the external electric field, they can be divided into four types, namely linear dielectrics (LD), ferroelectrics (FE), antiferroelectrics (AFE) and relaxor ferroelectrics (RFE). Generally, linear dielectrics have high energy storage efficiency and breakdown resistance, but due to their relatively low maximum polarization strength, their use in high energy storage applications is limited. Ferroelectrics have a larger saturation polarization and moderate breakdown strength, but their large remanent polarization leads to lower energy storage density and reduced efficiency. Antiferroelectrics have a good energy storage density, but their low energy storage efficiency and large heat dissipation have always been factors that restrict their application and development. Relaxor ferroelectrics exhibit moderate anti-breakdown field strength, large maximum polarization and low remanent polarization, making them very suitable for high energy storage.

[0003] Among the many dielectric materials, bismuth ferrite (BiFeO3, BF) ceramics are a type of lead-free multiferroic material with excellent performance. Because it does not contain toxic lead elements and has a high Curie temperature (≈850℃), a large spontaneous polarization intensity (100μC / cm 2) and lower sintering temperature, it has received more attention in recent years. During the sintering process, BF ceramics often cause large leakage current and low breakdown electric field due to the volatilization of bismuth elements and the change of iron valence. Therefore, barium titanate (BaTiO3, BT) is often dissolved in BF ceramics to improve leakage current and breakdown electric field, thereby achieving the purpose of improving the electrical properties of BF-based ceramics. In addition, by regulating the content of BF and BT, a new type of bismuth ferrite-barium titanate (BF-BT) lead-free relaxor ferroelectric ceramic material can be synthesized. This type of relaxor ferroelectric has good energy storage density performance, and the body contains polar nano-microregions (PNRs), which makes this type of material have a lower hysteresis loop, corresponding to a higher energy storage efficiency. In addition, by introducing other dielectric chemicals into BF-BT lead-free relaxor ferroelectric ceramic materials, new materials with higher energy storage density can be formed, which have great application prospects in the field of energy storage. For example, the introduction of CaTiO3 into BF-BT lead-free relaxor ferroelectric ceramics can achieve higher energy storage performance (W) under an applied electric field of 380 kV / cm. rec =5.03J / cm 3 , η=89.7%). For another example, the introduction of Nd(Zn 0.5 Zr 0.5 )O3 can achieve an enhanced recoverable energy storage density W under a small external electric field (E = 240 kV / cm) rec =2.45J / cm 3 And a moderate energy storage efficiency η = 72%.

[0004] Although BF-BT-based lead-free relaxor ferroelectric ceramic materials have good energy storage controllability, most of the BF-BT-based energy storage ferroelectric ceramics reported so far still show large residual polarization intensity and low breakdown field strength, resulting in low energy storage density and efficiency, and there are also challenges in improving energy storage thermal stability and frequency stability. In addition, BF-BT-based ferroelectric ceramics have large grain sizes and many defects, which show poor mechanical properties, and will also limit the service stability, reliability and life of the device in complex environments. Developing BF-BT-based lead-free relaxor ferroelectric ceramic materials with both high energy storage performance and high mechanical properties from a new perspective will be a necessary task for the miniaturization, lightweight, high reliability and high stability of energy storage devices and energy conversion systems in the new era. Summary of the invention

[0005] Based on the fact that the current BF-BT based energy storage ferroelectric ceramics still show large residual polarization intensity, low breakdown field strength and poor mechanical properties, resulting in low energy storage density, low efficiency and poor service stability and reliability, and improving energy storage thermal stability and frequency stability also faces challenges. The purpose of the present invention is to provide a bismuth ferrite-barium titanate based lead-free energy storage relaxor ferroelectric ceramic material and its preparation method and application, by introducing a linear dielectric Ca 0.7 La 0.2 TiO3 (CLT) is used to regulate the microstructure, phase structure, domain structure and relaxivity of bismuth ferrite-barium titanate ferroelectric ceramics, so as to achieve the purpose of improving both energy storage performance and mechanical properties, and provide high-reliability candidate materials for the new generation of micro energy storage devices and energy conversion systems.

[0006] The present invention is achieved through the following technical solutions:

[0007] In the first aspect, the present application provides a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material, the chemical formula of the bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material is (1-x)(0.67BiFeO3-0.33BaTiO3)-xCa 0.7 La 0.2 TiO3, wherein x=0.25-0.40, x represents the mole fraction. Specifically, x can be 0.25 or 0.30 or 0.35 or 0.40.

[0008] The present invention uses the third component solid solution method to convert the linear dielectric Ca 0.7 La 0.2 TiO3(CLT) was introduced into BF-BT lead-free relaxor ferroelectric ceramics, and a new multi-component solid solution lead-free energy storage relaxor ferroelectric ceramic material was synthesized by traditional solid phase reaction method: (1-x)(0.67BiFeO3-0.33BaTiO3)-xCa 0.7 La 0.2 TiO3 (abbreviated as BF-BT-xCLT, x = 0.25 ~ 0.40). The design aims to regulate the microstructure, phase structure, domain structure and relaxivity of BF-BT ceramics by solid solution of the third component, so as to achieve the purpose of improving energy storage and mechanical properties. The results show that the introduction of linear dielectric CLT can greatly reduce the grain size of the BF-BT ceramic material system and form polar nano-microregions PNRs with excellent kinetic characteristics, resulting in enhanced electric field breakdown resistance, relaxivity and resistance to plastic deformation of the ceramic material, thereby obtaining enhanced energy storage performance and mechanical properties. When x = 0.30, the BF-BT-based lead-free relaxor ferroelectric ceramics obtained an excellent recoverable energy storage density W under a small electric field (390kV / cm). rec =5.47J / cm3 , enhanced energy storage efficiency η = 72.26%, good thermal stability (25 to 100 ° C) and frequency stability (1 to 500 Hz) and ultra-high mechanical hardness H v =6.9GPa; when x=0.40, the energy storage efficiency η of BF-BT-based lead-free relaxor ferroelectric ceramics is as high as 81.10%. These performance indicators far exceed the energy storage performance and mechanical properties of pure BF-BT lead-free ferroelectric ceramics and many lead-free ferroelectric energy storage material systems. This new type of BF-BT-based lead-free relaxor ferroelectric ceramic material with excellent energy storage performance and mechanical properties is expected to be used in a new generation of miniaturized, lightweight, highly reliable and highly stable energy storage devices and energy conversion systems, making important contributions to the new era of energy and electronic devices as well as human development and progress.

[0009] In a second aspect, the present application provides a method for preparing a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material, comprising the following steps:

[0010] (1) weighing chemical reagents Bi2O3, Fe2O3, TiO2, La2O3, BaCO3 and CaCO3 according to the chemical formula of bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic materials to prepare powders;

[0011] (2) using the powder to perform granulation molding to prepare a disc body;

[0012] (3) performing a debinding process on the disc blank;

[0013] (4) sintering the debinding disc green body to obtain a disc ceramic material;

[0014] (5) The sintered disc ceramic material is subjected to silver plating and polarization treatment to obtain bismuth ferrite-barium titanate based lead-free energy storage relaxor ferroelectric ceramic material (BF-BT-xCLT ceramic).

[0015] Furthermore, when preparing the powder in step (1), the weighed chemical reagent is first ball-milled, then dried, and then pre-calcined. After pre-calcination, it is ball-milled again, and then the slurry is taken out and dried into powder.

[0016] Furthermore, the temperature during the pre-sintering treatment is controlled at 800° C. to 850° C., and the holding time is 2 h to 3 h.

[0017] Furthermore, when preparing the disc blank in step (2), a polyvinyl alcohol binder is added to the obtained powder for stirring and granulation, and the powder is sieved after granulation, and then pressed into tablets on a powder dry pressing machine.

[0018] Furthermore, the prepared disc blank has a diameter of 12 mm and a thickness of 0.8 mm to 1.4 mm.

[0019] Furthermore, the debinding process in step (3) includes the following three stages:

[0020] The first stage was to heat from room temperature to 120°C at a rate of 1°C / min and keep the temperature for 2h;

[0021] The second stage was to heat up to 450℃ at a rate of 1℃ / min and keep the temperature for 4h;

[0022] The third stage is to heat the temperature to 600℃ at a rate of 1℃ / min and keep it for 4h, then cool it naturally to room temperature.

[0023] Furthermore, in step (4), the disc green body is covered with powder by buried firing; the sintering temperature is 1040° C. to 1100° C., and the temperature is kept for 3 hours.

[0024] Furthermore, before electrode plating, the upper and lower surfaces of the ceramic material are first polished, and then the polished ceramic is cleaned and dried, a layer of silver paste is coated on the upper and lower surfaces of the dried ceramic sheet, and then it is placed in an oven to dry, and finally the ceramic is placed in a muffle furnace for silver sintering to obtain bismuth ferrite-barium titanate based lead-free energy storage relaxor ferroelectric ceramic material (BF-BT-xCLT ceramic).

[0025] In a third aspect, the present application provides an application of a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material, including application in a new generation of miniaturized, lightweight, highly reliable and highly stable energy storage devices and energy conversion systems.

[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0027] (1) The present invention has obtained unique microstructural characteristics: by introducing linear dielectric CLT into BF-BT-based lead-free relaxor ceramics through the third component solid solution method, it can effectively regulate the coexistence structure of rhombohedral phase (R3c) and pseudo cubic phase (Pm-3m), destroy the long-range ordered ferroelectric domain structure, and form polar nano-microregions PNRs with excellent dynamic characteristics, which helps to improve the maximum polarization intensity and reduce the residual polarization intensity and increase the relaxation behavior. At the same time, the microstructure grain size of the ceramic is greatly reduced, and the defects and porosity are low, which greatly improves the ceramic's ability to withstand breakdown and resist mechanical plastic deformation, helps to improve energy storage and mechanical properties at the same time, and provides technical reference for the development of energy storage materials with high energy storage performance and high mechanical properties.

[0028] (2) The present invention obtains excellent energy storage performance: by introducing a linear dielectric CLT into the BF-BT matrix, the optimal component x = 0.30, the recoverable energy storage density (W) obtained under a small electric field (390 kV / cm) rec) up to 5.47J / cm 3 , the energy storage efficiency (η) is as high as 72.26%; when x = 0.40, the energy storage efficiency η of BF-BT-based lead-free relaxor ferroelectric ceramics is as high as 81.10%. This patent can provide a promising alternative material for energy storage devices and energy conversion systems in actual work, and is also expected to be applied to a new generation of miniaturized, lightweight, highly reliable and highly stable energy storage devices and energy conversion systems, making important contributions to the new era of energy and electronic devices and human development and progress.

[0029] (3) The present invention achieves enhanced energy storage stability: by introducing a linear dielectric CLT into the BF-BT matrix, the optimal component x = 0.30, the energy storage performance maintains good stability at a test frequency of 1-500 Hz, for example, the recoverable energy storage density only decreases by ΔW rec <4.2%, and the energy storage efficiency only decreased by Δη<4.19%. At the test temperature of 25℃-100℃, its energy storage performance also maintained good stability. For example, the recoverable energy storage density only decreased by ΔW rec <12.54%, and the energy storage efficiency is only reduced by Δη<19.33%. The enhanced energy storage stability can lay the foundation for the long service life of ceramic materials.

[0030] (4) The present invention obtains ultra-high mechanical properties: by introducing linear dielectric CLT into the BF-BT based system, its optimal component x = 0.30 exhibits excellent resistance to plastic deformation and obtains an ultra-high mechanical hardness value H v =6.9GPa. The ultra-high mechanical behavior can lay the foundation for the reliability and stability of ceramic materials in resisting external interference in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0032] Figure 1 The technical roadmap for preparing BF-BT-xCLT ceramics in the embodiments of the present invention and the performance comparison diagram of BF-BT-xCLT ceramics and many lead-free energy storage ceramic materials; (a) is the technical roadmap, (b) is the performance comparison diagram of BF-BT-xCLT ceramics and many lead-free energy storage ceramic materials;

[0033] Figure 2The crystal structure and domain structure of the BF-BT-xCLT ceramic in the embodiment of the present invention; (a) is the XRD spectrum of the BF-BT-xCLT ceramic, (b) and (c) are local enlarged views of the (111) and (200) diffraction peaks in the XRD spectrum, (d) is a TEM image; (e) is a PFM image;

[0034] Figure 3 The microstructure diagram of the BF-BT-xCLT ceramic in the embodiment of the present invention; wherein (ad) is the SEM micrograph of the thermally etched surface of the BF-BT-xCLT ceramic, and the inset is the grain size distribution diagram;

[0035] Figure 4 Graphs showing the dielectric behavior and relaxation behavior of BF-BT-xCLT ceramics in an embodiment of the present invention; wherein (a) is a dielectric-temperature spectrum of BF-BT-xCLT ceramics, and (b) is a dielectric-temperature curve fitted using a modified Curie-Weiss theorem;

[0036] Figure 5 1 is a diagram showing the hysteresis curve and energy storage behavior of the BF-BT-xCLT ceramic in the embodiment of the present invention; wherein (a) is the hysteresis curve obtained by the BF-BT-xCLT ceramic under different electric fields, and (b) is the change of the recoverable energy storage density and energy storage efficiency of the BF-BT-xCLT ceramic with the components;

[0037] Figure 6 : is a frequency and temperature stability behavior diagram of the BF-BT-xCLT ceramic in an embodiment of the present invention; wherein (a) is a PE curve obtained by the optimal component x=0.30 ceramic at a test frequency of 1-500Hz, (b) is the polarization intensity, recoverable energy storage density and energy storage efficiency obtained at different test frequencies, (c) is a PE curve obtained by the optimal component x=0.30 ceramic at a test temperature of 25°C-100°C, and (d) is the recoverable energy storage density and energy storage efficiency obtained at different test temperatures;

[0038] Figure 7 Figure 3 is a diagram of the mechanical properties of BF-BT-xCLT ceramics in an embodiment of the present invention; wherein (a) is a load-displacement curve of a BF-BT-based relaxor ferroelectric ceramic with an optimal component x=0.30 tested under different loads, and (b) is a Vickers indentation scanning electron microscope image of a BF-BT-based relaxor ferroelectric ceramic with an optimal component x=0.30. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.

[0040] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] The present invention uses the third component solid solution method to convert the linear dielectric Ca 0.7 La 0.2 TiO3 (CLT) is introduced into BF-BT lead-free relaxor ferroelectric ceramics, thereby regulating the microstructure, phase structure, domain structure and relaxivity of BF-BT ceramics, and finally achieving the purpose of improving energy storage and mechanical properties. When x = 0.30, BF-BT-based lead-free relaxor ferroelectric ceramics achieve an excellent recoverable energy storage density W under a small electric field (390kV / cm). rec =5.47J / cm 3 , enhanced energy storage efficiency η = 72.26%, good thermal stability (25 to 100 ° C) and frequency stability (1 to 500 Hz) and ultra-high mechanical hardness H v =6.9GPa; when x=0.40, the energy storage efficiency η of BF-BT-based lead-free relaxor ferroelectric ceramics is as high as 81.10%. These performance indicators far exceed the energy storage performance and mechanical properties of pure BF-BT lead-free ferroelectric ceramics and many lead-free ferroelectric energy storage material systems. This new type of BF-BT-based lead-free relaxor ferroelectric ceramic material with excellent energy storage performance and mechanical properties is expected to be used in a new generation of miniaturized, lightweight, highly reliable and highly stable energy storage devices and energy conversion systems, making important contributions to the new era of energy and electronic devices as well as human development and progress.

[0042] Among them, the performance characterization method of the prepared BF-BT-xCLT ceramics is:

[0043] (1) Structural characterization method of BF-BT-xCLT ceramics:

[0044] X-ray diffractometer (XRD) was used to characterize the crystal structure and phase structure of BF-BT-xCLT ceramics. Cu target Kα ray was used, the test angle range (2θ) was 20°-80°, and the scanning speed was 2° / min. Transmission electron microscopy (TEM) was used to observe the domain size, domain distribution and domain structure characteristics of BF-BT-xCLT ceramics at an accelerating voltage of 200kV. For TEM characterization, BF-BT-xCLT ceramics must first undergo mechanical polishing, and then be thinned using an ion gun voltage of 5kV on an ion thinning instrument. After a small hole is formed, the ion gun voltage is reduced to 3.5kV and thinned for 30 minutes to obtain a TEM sample. Scanning electron microscopy (SEM) was used to observe the surface microstructure of the ceramic sample after thermal etching, and the average grain size of the sample was calculated. Piezoelectric force microscopy (PFM) was used to observe the domain size, domain distribution and domain structure characteristics of BF-BT-xCLT ceramics, and its piezoelectric response was analyzed.

[0045] (2) Characterization methods of electrical and mechanical properties of BF-BT-xCLT ceramics:

[0046] The relationship between the dielectric constant and dielectric loss of BF-BT-xCLT ceramics and temperature was measured using a high-temperature dielectric thermometer. The test temperature was 35℃~450℃. Then, the modified Curie-Weiss theorem was used to fit the dielectric-temperature curve to obtain the relaxation properties of BF-BT-xCLT ceramics. The hysteresis (PE) curve of BF-BT-xCLT ceramics was tested under different electric fields (30-390kV / cm) using a ferroelectric analyzer to obtain the corresponding recoverable energy storage density (W rec ) and energy storage efficiency (η). In addition, the hysteresis (PE) curves of BF-BT-xCLT ceramics were obtained at different test frequencies (1Hz-500 Hz) and different temperatures (25℃-100℃), and their frequency stability and temperature stability were analyzed. The load-displacement curves and mechanical deformation of BF-BT-xCLT ceramics under different loads (10mN, 20mN, 30mN, 40mN and 50mN) were characterized by a nanoindenter, and the indentation morphology and mechanical deformation were analyzed by atomic force microscopy (AFM). The mechanical deformation and hardness of BF-BT-xCLT ceramics were characterized by a Vickers hardness tester. The indentation load was 1.961N and the load was maintained for 15s. The Vickers hardness was calculated by measuring the average length of the indentation diagonal. Before performing nanoindentation and Vickers indentation tests, the surface of BF-BT-xCLT ceramics needs to be polished. First use 1000-grit coarse sandpaper, then 4000-grit fine sandpaper, and finally use diamond particles to polish until it reaches the requirement of 0.05μm.

[0047] The specific implementation cases of BF-BT-xCLT ceramics under each component are as follows:

[0048] Example 1

[0049] This embodiment provides a method for preparing BF-BT-0.25CLT lead-free relaxor ferroelectric ceramics. The preparation process is as follows: Figure 1 As shown, follow these steps:

[0050] S1. Prepare chemical reagents: Bi2O3 (AR 99%), Fe2O3 (AR 99%), TiO2 (AR 99%), La2O3 (AR99.9%), BaCO3 (AR 99%) and CaCO3 (AR 99%).

[0051] S2, the chemical reagents in step S1 are adjusted according to 0.75 (0.67BiFeO3-0.33BaTiO3)-0.25Ca 0.7 La 0.2 TiO3 (BF-BT-0.25CLT for short) was weighed on a high-precision analytical balance, and then the powder mixture was placed in a polytetrafluoroethylene ball milling jar, with anhydrous ethanol as the dispersion medium, and milled with a planetary ball mill for 20-24 h at a speed of 215 r / min to fully mix the chemical reagents.

[0052] S3. Take out the highly mixed BF-BT-0.25CLT slurry and dry it in a high-temperature furnace. Put the dried powder in an alumina crucible, cover the crucible lid and put it in a muffle furnace for pre-sintering. The pre-sintering temperature is set to 850°C and kept warm for 3 hours. A solid solution compound with a certain structure and a BF-BT-0.25CLT ceramic main crystal are obtained through solid-phase reaction. After pre-sintering, the powder is placed in a ball mill and milled on a planetary ball mill at a speed of 215r / min for 12-20 hours. Then the slurry is taken out and dried into powder.

[0053] S4. Add 7% polyvinyl alcohol (PVA) binder by mass to the obtained BF-BT-0.25CLT powder for stirring and granulation, and then pass through 80 mesh and 120 mesh screens respectively and press into tablets on a powder dry pressing machine. The molding pressure is set to 3-15MPa, and the powder is molded into a BF-BT-0.25CLT round tablet body with a diameter of 12mm and a thickness of 1mm.

[0054] S5. The BF-BT-0.25CLT disc blank is debinded in a muffle furnace. The debinding temperature is set from room temperature to 120°C at a heating rate of 1°C / min for 2 hours, then to 450°C at a heating rate of 1°C / min for 4 hours, and finally to 600°C at a heating rate of 1°C / min for 4 hours. After insulation, it is naturally cooled to room temperature. Then, the debinded BF-BT-0.25CLT disc blank is placed in a muffle furnace for sintering. Covering the disc blank with the corresponding powder by burying it can effectively prevent the volatilization of elements. The sintering temperature is set to 1040-1100°C, kept for 3 hours, and naturally cooled to room temperature to obtain the BF-BT-0.25CLT ceramic material.

[0055] S6. Polish the upper and lower surfaces of the BF-BT-0.25CLT ceramic material, then clean the polished ceramic in an ultrasonic cleaner for 10 minutes and dry it in a drying oven. After drying, apply a layer of high-quality silver paste on the upper and lower surfaces of the ceramic sheet, then place it in an oven at 120°C for 30 minutes, and finally place the ceramic in a muffle furnace for silver sintering. The temperature of the muffle furnace is set to: increase the heating rate to 550°C / min at a heating rate of 5°C / min, keep warm for 30 minutes, and then cool naturally to obtain BF-BT-0.25CLT ceramic material that meets electrical testing and engineering applications.

[0056] The following performance characteristics were performed on the BF-BT-0.25CLT ceramic material prepared by the method of this embodiment.

[0057] 1) The ceramic samples were tested by XRD and SEM, proving that the linear dielectric 0.25CLT component was successfully introduced into the BF-BT lattice. The ceramics exhibited a pure perovskite structure with a coexistence structure of rhombohedral phase (R3c) and pseudocubic phase (Pm-3m) ( Figure 2 At the same time, after introducing 0.25CLT into the matrix, it was found that the grain size of the ceramic sample was significantly reduced to 0.70μm, and the surface of the sample was very dense, with no obvious pores and defects ( Figure 3 ).

[0058] 2) The dielectric behavior and relaxation behavior of the ceramic samples were measured using a high-temperature dielectric thermometer. It was found that the relaxation degree of the BF-BT ceramic material was enhanced after the introduction of 0.25CLT component ( Figure 4 ), a larger relaxation fitting coefficient γ = 1.90 is obtained, which is beneficial to improve the energy storage performance.

[0059] 3) The hysteresis curve of the ceramic sample was tested by ferroelectric analysis to obtain the recoverable energy storage density (W) of the BF-BT-0.25CLT ceramic sample. rec) and energy storage efficiency (η), where the recoverable energy storage density (W rec ) is 2.89 J / cm 3 , the energy storage efficiency (η) is as high as 72.8% ( Figure 5 ).

[0060] Example 2

[0061] This embodiment provides a method for preparing BF-BT-0.30CLT lead-free relaxor ferroelectric ceramics. The preparation process is as follows: Figure 1 As shown, follow these steps:

[0062] S1. Prepare chemical reagents: Bi2O3 (AR 99%), Fe2O3 (AR 99%), TiO2 (AR 99%), La2O3 (AR99.9%), BaCO3 (AR 99%) and CaCO3 (AR 99%).

[0063] S2, the chemical reagents in step S1 are mixed according to the stoichiometric formula 0.70 (0.67BiFeO3-0.33BaTiO3)-0.30Ca 0.7 La 0.2 TiO3 (BF-BT-0.30CLT for short) was weighed on a high-precision analytical balance, and then the powder mixture was placed in a polytetrafluoroethylene ball milling jar, with anhydrous ethanol as the dispersion medium, and milled with a planetary ball mill for 20-24 h at a speed of 215 r / min to fully mix the chemical reagents.

[0064] S3. Take out the highly mixed BF-BT-0.30CLT slurry and dry it in a high-temperature furnace. Put the dried powder in an alumina crucible, cover the crucible lid and put it in a muffle furnace for pre-sintering. The pre-sintering temperature is set to 850°C and kept warm for 3 hours. A solid solution compound with a certain structure and a BF-BT-0.30CLT ceramic main crystal are obtained through solid-phase reaction. After pre-sintering, the powder is placed in a ball mill and milled on a planetary ball mill at a speed of 215r / min for 12-20 hours. Then the slurry is taken out and dried into powder.

[0065] S4. Add 7% polyvinyl alcohol (PVA) binder by mass to the obtained BF-BT-0.30CLT powder for stirring and granulation, and then pass through 80 mesh and 120 mesh screens respectively and press into tablets on a powder dry pressing machine. The molding pressure is set to 3-15MPa, and the powder is molded into a BF-BT-0.30CLT round tablet body with a diameter of 12mm and a thickness of 1mm.

[0066] S5. The BF-BT-0.30CLT disc blank is debinded in a muffle furnace. The debinding temperature is set from room temperature to 120°C at a heating rate of 1°C / min for 2 hours, then to 450°C at a heating rate of 1°C / min for 4 hours, and finally to 600°C at a heating rate of 1°C / min for 4 hours. After insulation, it is naturally cooled to room temperature. Then, the debinded BF-BT-0.30CLT disc blank is placed in a muffle furnace for sintering. Covering the disc blank with the corresponding powder by burying can effectively prevent the volatilization of elements. The sintering temperature is set to 1040-1100°C, kept for 3 hours, and naturally cooled to room temperature to obtain the BF-BT-0.30CLT ceramic material.

[0067] S6. Polish the upper and lower surfaces of the BF-BT-0.30CLT ceramic material, then clean the polished ceramic in an ultrasonic cleaner for 10 minutes and dry it in a drying oven. After drying, apply a layer of high-quality silver paste on the upper and lower surfaces of the ceramic sheet, then place it in an oven at 120°C for 30 minutes, and finally place the ceramic in a muffle furnace for silver sintering. The temperature of the muffle furnace is set to: increase the heating rate to 550°C / min at a heating rate of 5°C / min, keep warm for 30 minutes, and then cool naturally to obtain BF-BT-0.30CLT ceramic material that meets electrical testing and engineering applications.

[0068] The following performance characteristics were performed on the BF-BT-0.30CLT ceramic material prepared by the method of this embodiment.

[0069] 1) The ceramic samples were tested by XRD (using Cu target Kα rays, test angle range (2θ) 20°-80°, scanning speed 2° / min), proving that the linear dielectric 0.30CLT component was successfully introduced into the BF-BT lattice, and the ceramics showed a pure perovskite structure with a coexistence structure of rhombohedral phase (R3c) and pseudocubic phase (Pm-3m) ( Figure 2 ). By observing the domain structure of the ceramic sample by TEM (accelerating voltage of 200kV) and PFM, it was found that the ceramic body has uniformly distributed polar nano-microdomains PNRs ( Figure 2 ). Polar nano-microregion PNRs with excellent kinetic characteristics help to increase the maximum polarization strength, reduce the residual polarization strength and enhance the relaxation behavior, which is an important contribution to optimizing energy storage performance. At the same time, the ceramic samples were tested using SEM. After introducing 0.30CLT components into the matrix, it was found that the grain size of the ceramic samples was significantly reduced to 0.63μm. The surface of the sample was very dense, with no obvious visible pores and defects ( Figure 3). Among them, BF-BT-0.30CLT ceramic material has the smallest grain size, which greatly improves the ceramic's ability to withstand breakdown and resist mechanical plastic deformation, and helps to improve both energy storage and mechanical properties.

[0070] 2) The dielectric behavior and relaxation behavior of the ceramic samples were measured using a high-temperature dielectric thermometer. It was found that the relaxation degree of the BF-BT ceramic material was enhanced by introducing 0.30CLT components ( Figure 4 ), and a larger relaxation fitting coefficient γ = 1.92 was obtained. Among them, the BF-BT-0.30CLT ceramic material has the largest relaxation fitting coefficient, corresponding to the largest relaxation behavior, which helps to improve the energy storage performance.

[0071] 3) The hysteresis curve of the ceramic sample was tested by ferroelectric analysis to obtain the recoverable energy storage density (W) of the BF-BT-0.30CLT ceramic sample. rec ) and energy storage efficiency (η). Among them, the recoverable energy storage density (W rec ) up to 5.47J / cm 3 , the energy storage efficiency (η) is as high as 72.26% ( Figure 5 ), and the breakdown electric field is increased to 390kV / cm. Among all the components, x=0.03 has the largest recoverable energy storage density and good energy storage efficiency. At the same time, this energy storage performance far exceeds the energy storage performance of pure BF-BT lead-free ferroelectric ceramics and many lead-free ferroelectric energy storage material systems ( Figure 1 ), can provide a promising alternative material for energy storage devices and energy conversion systems in actual work, and is also expected to be applied to a new generation of miniaturized, lightweight, highly reliable and highly stable energy storage devices and energy conversion systems, making important contributions to the energy and electronic devices of the new era and the progress of human development.

[0072] 4) The energy storage performance of the BF-BT-0.30CLT ceramic sample maintained excellent stability at the test frequency of 1-500Hz, and the recoverable energy storage density only decreased by ΔW rec <4.2%, and the energy storage efficiency only decreased by Δη<4.19%. At the test temperature of 25℃-100℃, its energy storage performance also maintained good stability, and the recoverable energy storage density only decreased by ΔW rec <12.54%, the energy storage efficiency only decreased by Δη<19.33% ( Figure 6 ). The excellent energy storage stability can lay the foundation for the long service life of ceramic materials.

[0073] 5) The mechanical properties of BF-BT-0.30CLT ceramic samples were tested using a nanoindenter and a Vickers indenter. The ceramic samples exhibited different deformation behaviors under different loads. The results showed that BF-BT-0.30CLT ceramics have good resistance to plastic deformation and have obtained an ultra-high mechanical hardness of H v =6.9GPa( Figure 7 ). The ultra-high mechanical behavior can lay the foundation for the reliability and stability of ceramic materials in resisting external interference in practical applications.

[0074] Example 3

[0075] This embodiment provides a method for preparing a BF-BT-0.35CLT lead-free relaxor ferroelectric ceramic. The preparation process is as follows: Figure 1 As shown, follow these steps:

[0076] S1. Prepare chemical reagents: Bi2O3 (AR 99%), Fe2O3 (AR 99%), TiO2 (AR 99%), La2O3 (AR99.9%), BaCO3 (AR 99%) and CaCO3 (AR 99%).

[0077] S2, the chemical reagents in step S1 are mixed according to the stoichiometric formula 0.65 (0.67BiFeO3-0.33BaTiO3)-0.35Ca 0.7 La 0.2 TiO3 (BF-BT-0.35CLT for short) was weighed on a high-precision analytical balance, and then the powder mixture was placed in a polytetrafluoroethylene ball milling jar, with anhydrous ethanol as the dispersion medium, and milled with a planetary ball mill for 20-24 h at a speed of 215 r / min to fully mix the chemical reagents.

[0078] S3. Take out the highly mixed BF-BT-0.35CLT slurry and dry it in a high-temperature furnace. Put the dried powder in an alumina crucible, cover the crucible lid and put it in a muffle furnace for pre-sintering. The pre-sintering temperature is set to 850°C and kept warm for 3 hours. A solid solution compound with a certain structure and a BF-BT-0.35CLT ceramic main crystal are obtained through solid-phase reaction. After pre-sintering, the powder is placed in a ball mill and milled on a planetary ball mill at a speed of 215r / min for 12-20 hours. Then the slurry is taken out and dried into powder.

[0079] S4. Add 7% polyvinyl alcohol (PVA) binder by mass to the obtained BF-BT-0.35CLT powder for stirring and granulation, and then pass through 80 mesh and 120 mesh screens respectively and press into tablets on a powder dry pressing machine. The molding pressure is set to 3-15MPa, and the powder is molded into a BF-BT-0.35CLT round tablet body with a diameter of 12mm and a thickness of 1mm.

[0080] S5. The BF-BT-0.35CLT disc blank is debinded in a muffle furnace. The debinding temperature is set from room temperature to 120°C at a heating rate of 1°C / min for 2 hours, then to 450°C at a heating rate of 1°C / min for 4 hours, and finally to 600°C at a heating rate of 1°C / min for 4 hours. After insulation, it is naturally cooled to room temperature. Then, the debinded BF-BT-0.35CLT disc blank is placed in a muffle furnace for sintering. Covering the disc blank with the corresponding powder by burying it can effectively prevent the volatilization of elements. The sintering temperature is set to 1040-1100°C, kept for 3 hours, and naturally cooled to room temperature to obtain the BF-BT-0.35CLT ceramic material.

[0081] S6. Polish the upper and lower surfaces of the BF-BT-0.35CLT ceramic material, then clean the polished ceramic in an ultrasonic cleaner for 10 minutes and dry it in a drying oven. After drying, apply a layer of high-quality silver paste on the upper and lower surfaces of the ceramic sheet, then place it in an oven at 120°C for 30 minutes, and finally place the ceramic in a muffle furnace for silver sintering. The temperature of the muffle furnace is set to: increase the heating rate to 550°C / min at a heating rate of 5°C / min, keep warm for 30 minutes, and then cool naturally to obtain BF-BT-0.35CLT ceramic material that meets electrical testing and engineering applications.

[0082] The following performance characteristics were performed on the BF-BT-0.35CLT ceramic material prepared by the method of this embodiment.

[0083] 1) XRD and SEM were used to test the ceramic samples, proving that the linear dielectric 0.35CLT component was successfully introduced into the BF-BT lattice. The ceramics showed a pure perovskite structure with a coexistence structure of rhombohedral phase (R3c) and pseudocubic phase (Pm-3m), but at this time the pseudocubic phase (Pm-3m) was dominant ( Figure 2 At the same time, after introducing 0.35CLT into the matrix, it was found that the grain size of the ceramic sample was significantly reduced to 0.65μm, and the surface of the sample was very dense, with no obvious pores and defects ( Figure 3 ).

[0084] 2) The dielectric behavior and relaxation behavior of the ceramic samples were measured using a high-temperature dielectric thermometer. It was found that the relaxation degree of the BF-BT ceramic material was enhanced after the introduction of 0.35CLT component ( Figure 4 ), a larger relaxation fitting coefficient γ = 1.84 is obtained, which is beneficial to improve the energy storage performance.

[0085] 3) The hysteresis curve of the ceramic sample was tested by ferroelectric analysis to obtain the recoverable energy storage density (W) of the BF-BT-0.35CLT ceramic sample. rec ) and energy storage efficiency (η), where the recoverable energy storage density (W rec ) is 2.51 J / cm 3 , the energy storage efficiency (η) is as high as 79.22% ( Figure 5 ).

[0086] Example 4

[0087] This embodiment provides a method for preparing a BF-BT-0.40CLT lead-free relaxor ferroelectric ceramic. The preparation process is as follows: Figure 1 As shown, follow these steps:

[0088] S1. Prepare chemical reagents: Bi2O3 (AR 99%), Fe2O3 (AR 99%), TiO2 (AR 99%), La2O3 (AR99.9%), BaCO3 (AR 99%) and CaCO3 (AR 99%).

[0089] S2, the chemical reagents in step S1 are mixed according to the stoichiometric formula 0.60 (0.67BiFeO3-0.33BaTiO3)-0.40Ca 0.7 La 0.2 TiO3 (BF-BT-0.40CLT for short) was weighed on a high-precision analytical balance, and then the powder mixture was placed in a polytetrafluoroethylene ball milling jar, with anhydrous ethanol as the dispersion medium, and milled with a planetary ball mill for 20-24 h at a speed of 215 r / min to fully mix the chemical reagents.

[0090] S3. Take out the highly mixed BF-BT-0.40CLT slurry and dry it in a high-temperature furnace. Put the dried powder in an alumina crucible, cover the crucible lid and put it in a muffle furnace for pre-sintering. The pre-sintering temperature is set to 850°C and kept warm for 3 hours. A solid solution compound with a certain structure and a BF-BT-0.40CLT ceramic main crystal are obtained through solid-phase reaction. After pre-sintering, the powder is placed in a ball mill and milled on a planetary ball mill at a speed of 215r / min for 12-20 hours, and then the slurry is taken out and dried into powder.

[0091] S4. Add 7% polyvinyl alcohol (PVA) binder by mass to the obtained BF-BT-0.40CLT powder for stirring and granulation, and then pass through 80 mesh and 120 mesh screens respectively and press into tablets on a powder dry pressing machine. The molding pressure is set to 3-15MPa, and the powder is molded into a BF-BT-0.40CLT round tablet body with a diameter of 12mm and a thickness of 1mm.

[0092] S5. The BF-BT-0.40CLT disc blank is debinded in a muffle furnace. The debinding temperature is set from room temperature to 120°C at a heating rate of 1°C / min for 2 hours, then to 450°C at a heating rate of 1°C / min for 4 hours, and finally to 600°C at a heating rate of 1°C / min for 4 hours. After insulation, it is naturally cooled to room temperature. Then, the debinded BF-BT-0.40CLT disc blank is placed in a muffle furnace for sintering. Covering the disc blank with the corresponding powder by burying can effectively prevent the volatilization of elements. The sintering temperature is set to 1040-1100°C, kept for 3 hours, and naturally cooled to room temperature to obtain the BF-BT-0.40CLT ceramic material.

[0093] S6. Polish the upper and lower surfaces of the BF-BT-0.40CLT ceramic material, then clean the polished ceramic in an ultrasonic cleaner for 10 minutes and dry it in a drying oven. After drying, apply a layer of high-quality silver paste on the upper and lower surfaces of the ceramic sheet, then place it in an oven at 120°C for 30 minutes, and finally place the ceramic in a muffle furnace for silver sintering. The temperature of the muffle furnace is set to: increase the heating rate to 550°C / min at a heating rate of 5°C / min, keep warm for 30 minutes, and then cool naturally to obtain BF-BT-0.40CLT ceramic material that meets electrical testing and engineering applications.

[0094] The following performance characteristics were performed on the BF-BT-0.40CLT ceramic material prepared by the method of this embodiment.

[0095] 1) XRD and SEM were used to test the ceramic samples, proving that the linear dielectric 0.40CLT component was successfully introduced into the BF-BT lattice, and the ceramic showed a pure perovskite structure. At this time, the crystal structure is a pseudo-cubic phase (Pm-3m) structure ( Figure 2 At the same time, after introducing 0.40CLT into the matrix, it was found that the grain size of the ceramic sample was significantly reduced to 0.66μm, and the surface of the sample was very dense, with no obvious pores and defects ( Figure 3 ).

[0096] 2) The dielectric behavior and relaxation behavior of the ceramic samples were measured using a high-temperature dielectric thermometer. It was found that the relaxation degree of the BF-BT ceramic material was enhanced by introducing 0.40CLT components ( Figure 4 ), a larger relaxation fitting coefficient γ = 1.79 is obtained, which is beneficial to improve the energy storage performance.

[0097] 3) The hysteresis curve of the ceramic sample was tested by ferroelectric analysis to obtain the recoverable energy storage density (W) of the BF-BT-0.40CLT ceramic sample. rec ) and energy storage efficiency (η). Among them, the recoverable energy storage density (W rec ) is 2.63 J / cm 3 , the energy storage efficiency (η) is as high as 81.10% ( Figure 4 ). Among all the components, the BF-BT based relaxor ferroelectric ceramic material with x = 0.40 has the highest energy storage efficiency.

[0098] Based on the above test results, the optimal component in this case is x = 0.30. Figure 3 It can be seen that with the introduction of CLT, BF-BT-based ceramics are extremely dense and the grain size is greatly reduced. The average grain size is about 0.63-0.70um. Among them, the optimal component x=0.30 has the smallest grain size, which helps to improve the material's ability to withstand breakdown, thereby directly affecting the energy storage performance of the ceramic. At the same time, the reduction in grain size and the densification of the organizational structure can increase its hardness value, which is of great help to the optimization of mechanical properties. Figure 4 It can be seen that the relaxor ferroelectric ceramic with the optimal component x = 0.30 has the largest relaxation fitting coefficient γ = 1.92, indicating that it has the largest relaxation behavior. Figure 5 It can be seen that for the relaxor ferroelectric ceramic with the optimal component x = 0.30, an excellent recoverable energy storage density (W rec =5.47J / cm 3 ) and energy storage efficiency (η=72.26%); when x=0.40, the energy storage efficiency η of BF-BT based lead-free relaxor ferroelectric ceramics is as high as 81.10%. Figure 6 It can be seen that the recoverable energy storage density of the relaxor ferroelectric ceramic with the optimal component x = 0.30 only decreases by ΔW at different test frequencies. rec <4.2%, and the energy storage efficiency only decreased by Δη<4.19%, indicating that it has excellent frequency stability. The relaxor ferroelectric ceramic with the optimal component x=0.30 has a recoverable energy storage density that only decreases by ΔW at different test temperatures. rec <12.54%, the energy storage efficiency only decreased by Δη<19.33%, indicating that it has good temperature stability. Figure 7It can be seen that the BF-BT-based relaxor ferroelectric ceramics with the optimal component x = 0.30 have different mechanical deformations and maximum indentation depths under different loads. The inset is the indentation morphology and plastic deformation behavior obtained under AFM testing, and the indentation depth is 318nm. From the Vickers indentation scanning electron microscopy image of the BF-BT-based relaxor ferroelectric ceramics with the optimal component x = 0.30, it can be seen that a force of 1.961N is applied to the sample and the load is maintained for 15s. The final hardness value of the ceramic is calculated to be H v =6.9Gpa.

[0099] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material, characterized in that: The chemical formula of the bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material is (1-x)(0.67BiFeO3-0.33BaTiO3)-xCa 0.7 La 0.2 TiO3, wherein x=0.25-0.40, x represents the molar fraction.

2. A method for preparing the bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material according to claim 1, characterized in that: The following steps are involved: (1) weighing chemical reagents Bi2O3, Fe2O3, TiO2, La2O3, BaCO3 and CaCO3 according to the chemical formula of bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic materials to prepare powders; (2) using the powder to perform granulation molding to prepare a disc body; (3) performing a debinding process on the disc blank; (4) sintering the debinding disc green body to obtain a disc ceramic material; (5) The sintered disc ceramic material is subjected to silver plating and polarization treatment to obtain bismuth ferrite-barium titanate based lead-free energy storage relaxation ferroelectric ceramic material.

3. The method for preparing a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material according to claim 2, characterized in that: When preparing the powder in step (1), the weighed chemical reagent is first ball-milled, then dried, and then pre-calcined. After pre-calcination, it is ball-milled again, and then the slurry is taken out and dried into powder.

4. The method for preparing a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material according to claim 3, characterized in that: The temperature during the pre-sintering treatment is controlled at 800°C to 850°C, and the insulation time is 2h to 3h.

5. The method for preparing a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material according to claim 2, characterized in that: When preparing the disc blank in step (2), polyvinyl alcohol binder is added to the obtained powder for stirring and granulation. After granulation, the powder is sieved and then pressed into tablets on a powder dry pressing machine.

6. The method for preparing a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material according to claim 5, characterized in that: The prepared disc blank has a diameter of 12 mm and a thickness of 0.8 mm to 1.4 mm.

7. The method for preparing a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material according to claim 2, characterized in that: The debinding process in step (3) includes the following three stages: The first stage was to heat from room temperature to 120°C at a rate of 1°C / min and keep the temperature for 2h; The second stage was to heat up to 450℃ at a rate of 1℃ / min and keep the temperature for 4h; The third stage is to heat the temperature to 600℃ at a rate of 1℃ / min and keep it for 4h, then cool it naturally to room temperature.

8. The method for preparing a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material according to claim 2, characterized in that: In step (4), the disc green body is covered with powder by buried firing; the sintering temperature is 1040° C. to 1100° C., and the temperature is kept for 3 hours.

9. The method for preparing a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material according to claim 2, characterized in that: Before electrode plating, the upper and lower surfaces of the ceramic material are first polished, and then the polished ceramic is cleaned and dried. A layer of silver paste is coated on the upper and lower surfaces of the dried ceramic sheet, and then it is placed in an oven to dry. Finally, the ceramic is placed in a muffle furnace for silver sintering to obtain a bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material.

10. An application of the bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material according to claim 1 or the bismuth ferrite-barium titanate-based lead-free energy storage relaxor ferroelectric ceramic material prepared by the preparation method according to any one of claims 2 to 9, characterized in that: Including applications in energy storage devices and energy conversion systems.

Citation Information

Patent Citations

  • Dielectric ceramic material, dielectric ceramic layer, preparation method of dielectric ceramic material and dielectric ceramic layer, and capacitor

    CN117637344A

  • Lead-free high-entropy ferroelectric ceramic material as well as preparation method and application thereof

    CN117735974A